Fate of leaf litter in restored Kandelia obovata (S. L.) mangrove forests with different ages in Jiulong River Estuary, China. Issue 2 (5th December 2019) - Chen, Jiahui; Chen, Guangcheng; Gu, Yantao; Zhu, Heng; Ye, Yong
Abstract : Ecological processing of leaf litter plays important roles in carbon dynamics of mangrove forests. Fate of leaf litter, that is, removal by crabs, microbial decomposition, and tidal export was quantified in two restored Kandelia obovata forests with ages of 24 years and 48 years, respectively, from December 2009 to November 2010. Crab abundance was also investigated to test the role of crabs in leaf litter processing. Daily leaf litter production was 1.064 ± 0.108 g C m −2 day −1 at the 24‐year forest and was 0.689 ± 0.040 g C m −2 day −1 at the 48‐year forest. Annual mean removal of leaf litter by crabs was lower at the 24‐year forest than at the 48‐year forest (0.177 ± 0.046 g C m −2 day −1 vs. 0.220 ± 0.050 g C m −2 day −1 ), due to a higher crab abundance at the older forest. Microbial decomposition and change in standing stock of leaf litter on the forest floor made a negligible contribution to the annual leaf litter production. Tidal exports of leaf litter were estimated as 0.875 ± 0.090 g C m −2 day −1 and 0.458 ± 0.086 g C m −2 day −1 at the 24‐year and 48‐year forests, respectively, accounting for 82.2% and 66.5% of their daily leaf litter production. Turnover rate of leaf litter was higher at the younger forest (1.7 ± 0.4 day −1 ) than the older forest (1.2 ± 0.3 day −1 ). Removal of leaf litter by crabs was higher in warm months while tidal export of leaf litter showed a much less apparent seasonal pattern. Spatial variations of crab removal and tidal export of leaf litter with forest zones were observed within each forest, while microbial decomposition of leaf litter was comparable among the different zones. These indicated that the ecosystem functions of restored mangrove forest could not reach a level equivalent to those of a mature forest even 24 years after restoration.